Pengaruh Storytelling dalam Pendidikan Personal Hygiene terhadap Kepatuhan Cuci Tangan Pakai Sabun pada Anak Usia 6-7 Tahun di Sekolah Dasar Negeri 13 Sesetan - Ni Nyoman Yudiarini; I Gusti Ayu Ratih Agustini; Claudia Wuri Prihandini (Poltekkes Kemenkes Malang, 2020)
Hand washing is one of the clean and healthy behaviors which has become a worldwide concern. Storytelling is one of the effective solutions to deliver health education to preschool students with the selection of appropriate tools depending on the method chosen, the childrens demand to learn, and the clients ability to learn. This study aimed to determine the effect of storytelling in personal hygiene education towards the compliance of hand washing with soap in children aged 6 until 7 years. This study was a pre experimental quantitative research with one groups pretest-posttest design. This study involved 32 respondents selected by total sampling technique. The compliance of hand washing with soap was measured using a questionnaire before and after the intervention. The results showed that the compliance of hand washing with soap during the pre test was mostly 87.5 percent in fewer adherences category. The majority of posttest compliance was 93.8 percent in the compliant category. Wilcoxon Sign Rank Test results obtained p value is 0.001. These results indicated that there was an effect of storytelling in personal hygiene education towards the compliance of hand washing with soap. It can be concluded that storytelling in personal hygiene education had a significant effect towards the compliance of hand washing with soap